2014
DOI: 10.1002/2013jb010623
|View full text |Cite
|
Sign up to set email alerts
|

Deformation of basaltic shield volcanoes under cointrusive stress permutations

Abstract: We performed a microstructural study of Piton des Neiges (La Réunion Island) to understand how intrusions and stresses control each other in basaltic volcanoes. Our study reveals that three perpendicular intrusions trends coexisted during the 2 Myr history of the volcano: a N120-140°E rift zone, a perpendicular dike trend, and swarms of subhorizontal intrusions hereafter called "sill zones". Independently, the inversion of fault-slip data shows that incompatible paleostress fields recurrently occurred along wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 131 publications
3
35
0
1
Order By: Relevance
“…The last known process that can be invoked to maintain a favourable stress field for dyking is the occurrence of a regional extension like in Iceland (Walker, 1993) or at Fuerteventura (Fernández et al, 2006). Chaput et al (2014a) recently showed from a thorough structural analysis carried out in Piton des Neiges that this volcano underwent a dominant NNE-SSW extension throughout its period of activity (i.e., between at least 2.2 and 0.03 Ma). The extension led to the development of a main N120-140 rift zone (Chevallier and Vatin-Perignon, 1982;Chaput et al, 2014a), parallel to the NW-SE rift zone and the South Volcanic Zone.…”
Section: Nw-se Rift Zone and South Volcanic Zone Related To The Deep mentioning
confidence: 99%
See 4 more Smart Citations
“…The last known process that can be invoked to maintain a favourable stress field for dyking is the occurrence of a regional extension like in Iceland (Walker, 1993) or at Fuerteventura (Fernández et al, 2006). Chaput et al (2014a) recently showed from a thorough structural analysis carried out in Piton des Neiges that this volcano underwent a dominant NNE-SSW extension throughout its period of activity (i.e., between at least 2.2 and 0.03 Ma). The extension led to the development of a main N120-140 rift zone (Chevallier and Vatin-Perignon, 1982;Chaput et al, 2014a), parallel to the NW-SE rift zone and the South Volcanic Zone.…”
Section: Nw-se Rift Zone and South Volcanic Zone Related To The Deep mentioning
confidence: 99%
“…Chaput et al (2014a) recently showed from a thorough structural analysis carried out in Piton des Neiges that this volcano underwent a dominant NNE-SSW extension throughout its period of activity (i.e., between at least 2.2 and 0.03 Ma). The extension led to the development of a main N120-140 rift zone (Chevallier and Vatin-Perignon, 1982;Chaput et al, 2014a), parallel to the NW-SE rift zone and the South Volcanic Zone. Moreover, our data reveal that the VT seismicity is not restricted to the massif of Piton de la Fournaise but also develops at the scale of La Réunion edifice (Fig.…”
Section: Nw-se Rift Zone and South Volcanic Zone Related To The Deep mentioning
confidence: 99%
See 3 more Smart Citations